EVALUASI PELAKSANAAN SISTEM DAN PROSEDUR PENERIMAAN KAS ( STUDI PADA DPPKAD KABUPATEN GRESIK ) - AMELIA, INNA RIZKY; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
Revenue, Finance and Assets Gresik Regional is suitable with the regulations which are described in local taxrevenue by using legitimate documents and involving the parties which are associated with the system and theprocedures for cash receipts has been carried out in accordance with the prevailing regulation. In addition, theoversight and the accountability system and procedures for cash receipts at the Departement of Revenue, Financeand Assets of Gresik Regency is transparent and accountable so that in the implementation of internal control inthe system and the procedures have already adequate. The research method is using qualitative descriptive analysismethod. It can be concluded that the implemtation of system and procedures for cash receipts are carried out at theDepartement of Revenue, Finance, and Assets Management of Gresik Regency has been carried out properly andsuitable with applicable regulations.Keywords : Implementation, System and Procedures, Cash ReceiptS, Internal Control.